Antipsychotic-Induced QT Prolongation and Torsade de Pointes in Patients with Mental Disorders: A Review - R. F. Nasyrova; A. V. Kidyaeva; M. M. Petrova; N. A. Shnayder (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2022)
INTRODUCTION. The high risk of life-threatening ventricular arrhythmias, particularly Torsade de Pointes (TdP), makes QT prolongation one of the most significant adverse drug reactions (ADRs) due to cardiotoxicity associated with antipsychotics (APs). AIM. This study aimed to systematise information on the effects of APs on QT interval duration and TdP risk in patients with mental disorders and to provide recommendations on preventive measures for practising psychiatrists and clinical pharmacologists.DISCUSSION. The authors searched information in PubMed, eLIBRARY.RU, and Google Scholar. The analysis included full-text articles on the results of placebo-controlled studies, crossover studies, case-control studies, systematic reviews, meta-analyses, and Cochrane reviews published from 1 September 2013 to 30 September 2023. The main mechanism of AP cardiotoxicity is the inhibition of voltage-gated ion channels (primarily potassium channels) in the cardiomyocyte membrane. Most first-generation APs are associated with dose-dependent QTc prolongation; thioridazine, chlorpromazine, and levomepromazine pose the highest risk of QTc prolongation and TdP. The results of this review do not support the hypothesis of a lower risk of QTc prolongation with next-generation APs than with first-generation APs. The correlation between serum AP levels and QTc prolongation severity is less characteristic of second- and third-generation APs. However, all second-generation APs lengthen the QTc interval and increase the risk of TdP, with clozapine and olanzapine posing the highest risk. Depending on the risk of QTc prolongation, APs can be divided into 3 groups: low-risk products (aripiprazole, lurasidone, cariprazine, paliperidone, and zuclopentixol), moderate-risk products (quetiapine, perphenazine, fluphenazine, olanzapine, clothiapine, and haloperidol), and high-risk products (chlorpromazine, promazine, clozapine, levomepromazine, and ziprasidone). The relationship between AP-induced QTс prolongation and TdP is ambiguous. If an AP exerts a homogeneous effect on cardiomyocytes, the risk of TdP remains low despite significant QTс prolongation.CONCLUSIONS. The summarised data on AP effects on QT interval duration and TdP risk in patients with mental disorders as well as the proposed recommendations for reducing TdP risk may be in demand by psychiatrists and clinical pharmacologists selecting AP and may help minimise the likelihood of potentially fatal AP-induced arrhythmogenic cardiac ADRs.